Emission wavelength red-shift by using "semi-bulk" InGaN buffer layer in InGaN/InGaN multiple-quantum-well. (December 2017) - Alam, Saiful; Sundaram, Suresh; Li, Xin; El Gmili, Youssef; Elouneg-Jamroz, Miryam; Robin, Ivan Christophe; Patriarche, Gilles; Salvestrini, Jean-Paul; Voss, Paul L.; Ougazzaden, Abdallah
Abstract: We report an elongation of emission wavelength by inserting a ∼70 nm thick high quality semi-bulk (SB) Iny Ga1-y N buffer layer underneath the Inx Ga1-x N/Iny Ga1-y N (x > y) multi-quantum-well (MQW).While the MQW structure without the InGaN SB buffer is fully strained on the n-GaN template, the MQW structure with the buffer has ∼15% relaxation. This small relaxation along with slight compositional pulling induced well thickness increase of MQW is believed to be the reason for the red-shift of emission wavelength. In addition, the SB InGaN buffer acts as an electron reservoir and also helps to reduce the Quantum Confined Stark Effect (QCSE) and thus increase the emission intensity. In this way, by avoiding fully relaxed buffer induced material degradation, a longer emission wavelength can be achieved by just using InGaN SB buffer while keeping all other growth conditions the same as the reference structure. Thus, a reasonably thick fully strained or very little relaxed InGaN buffer, which is realized by "semi-bulk" approach to maintain good InGaN material quality, can be beneficial for realizing LEDs, grown on top of this buffer, emitting in the blue to cyan to green regime without using excess indium (In). Highlights: In0.15 Ga0.85 N/In0.05 Ga0.95 N MQW are grown on fully strained ∼70 nm thick In0.05 Ga0.95 N "semi-bulk" buffer. An emission wavelength red-shift of ∼15 nm is observed both in CL and PL. This red-shift is important for overcoming the "green-gap" problem.